Influence of Feeding Different Maize Varieties on Production Performance and Egg Quality of White Leghorn Birds in India - Mishra, Ramkailash; Patel, Atul B.; Bhagora, Nikesh J.; Dhruv, Jitendra. J.; Savaliya, Fulabhai P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was carried out on 100 White Leghorn layer birds randomly divided into four treatments at the age of 20th week with 5 replicates in each (5 layers per replicate) and were fed treatment ration from 24th to 40th week of age. Four different layer rations (T1 to T4) were prepared by incorporating four different varieties of maize, viz., White maize-Gujarat Maize-3 (GM-3, T1), Gujarat Anand Yellow Maize Hybrid-1 (GAYMH-1, T2), High-Quality Protein Maize-1 (HQPM-1, T3) and Purple Maize (T4), respectively. The levels of lysine, tryptophan, carotenoid, total antioxidant activity (TAA), anthocyanin and protein were estimated in each maize variety and in treatment ration once as well as in eggs before and at different stages of the experiment (i.e., at 24th, 28th, 34th and 40th week of age). Egg production, egg weight, body weight, and feed consumption traits were recorded. Beta carotene, protein content and deep yellow color of egg yolk were significantly (p <0.05) higher in the eggs of White Leghorn layer birds which were fed layer ration prepared by using GAYMH-1 yellow maize variety (T2). However, oil content was significantly (p <0.05) higher in the eggs of birds fed layer ration prepared by using white maize (Gujarat maize-3) as compared to other varieties of maize. Significantly (p <0.05), higher contents of lysine, tryptophan, anthocyanin, and total antioxidant activity were observed in eggs of White Leghorn layer birds fed layer mash containing purple color maize compared to other varieties of maize.